Banking While Insolvent: Issues Faced by Insolvent Banking Customers Around Account Closure or Suspension - Robson, Carys; Stace, Victoria (Victoria University of Wellington Law Review, 2024)
This article presents evidence that suggests the major banks in New Zealand have had a practice of using their discretionary 'terms and conditions' powers to close or suspend the bank accounts of customers who go into an insolvency procedure. This can have a significant detrimental impact on the insolvent person and a blanket policy of this nature would not appear to be based on sound justification. This article suggests that an effective way to influence the banks' practices in this area could be through the conduct of financial institutions (CoFI) regime, expected to take effect in 2025.